QARAQALPAQ TILINDE GLYUTTONIYALÍQ DISKURSLARDÍ IZERTLEWDIŃ ÁHMIYETI - Nurlıbekova, G.M. (SCIENCE and SOCIETY, 2023)
In this article, the connection and difference between the concept of discourse and the concept of text, which is widely developed in modern linguistics, is highlighted based on the opinions of world linguists. Important issues of the study of the direction of discourse in the Karakalpak language, which began to appear after the 50s of the last century, are presented, directly connecting the gluttonous discourse to the culture of the people, the nation. Through the study of gluttonous discourses, it is noted as a huge tool that allows us to reveal the foundations of our culture, to determine the etymology of many words, and to show and introduce the nation’s life, cultural and spiritual wealth to the wider world, and justifies the need for research.